EXPLORING URBAN STREETSCAPE DESIGN: COMPREHENSIVE REVIEW OF SCIENTIFIC RESEARCH - Wang , K.; Shmelova-Nesterenko, O. (Art and Design, 2024)
The purpose: to analyse and synthesize research on urban street space and the evolution of urban streetscape design concepts, tracing their origins, development, classifications, and design practices. Methodology. The study conducts a historical and theoretical review of scientific and literary sources, employing methods of analysis, systematization, classification, and summarization of the obtained results. Results. Classical theories of designing public spaces, as well as the development of concepts related to spatial perception and a human-centric approach in design, have been examined and analysed. The interaction of these theories with big data and artificial intelligence in the research and design of urban public spaces has been identified, revealing that such collaboration accelerates the emergence of cutting-edge theoretical and practical innovations. Scientific novelty. Based on the analysis conducted, three main research directions in street space are identified and systematized: macro-level research, micro-level research, and research in urban design practices. Practical significance: The results of this research establish theoretical foundations and outline directions for the future development of studies in the field of street space design. They can be utilized by architects and urban designers in the process of planning and design.